Efficacy and Safety of Curcumin and Curcuma longa Extract in the Treatment of Arthritis: A Systematic Review and Meta-Analysis of Randomized Controlled Trial - Zeng, Liuting; Yang, Tiejun; Yang, Kailin; Yu, Ganpeng; Li, Jun; Xiang, Wang; Chen, Hua (Frontiers in Immunology, 2022)
Background: Modern pharmacological research found that the chemical components of Curcuma longa L. are mainly curcumin and turmeric volatile oil. Several recent randomized controlled trials (RCT) have shown that curcumin improves symptoms and inflammation in patients with arthritis. Methods: Pubmed, Cochran Library, CNKI, and other databases were searched to collect the randomized controlled trials (RCTs) of curcumin supplement in the treatment of RA. Then, the risk of bias of RCTs were assessed and data of RCTs were extracted. Finally, RevMan 5.3 was utilized for meta-analysis. Results: This systematic review and meta-analysis included 29 RCTs involving 2396 participants and 4 types of arthritis: Rheumatoid Arthritis (RA), Ankylosing Spondylitis (AS), Osteoarthritis (OA), and Juvenile idiopathic arthritis (JIA). Curcumin and Curcuma longa Extract is administered in a wide range of doses (120 mg-1500 mg) and durations (4-36 weeks). Overall, Curcumin and Curcuma longa Extract was well tolerated in all studies and improved the severity of inflammation and pain levels in these arthritis patients. However, more RCTs are needed in the future to elucidate the effect of Curcumin and Curcuma longa Extract supplementation in patients with arthritis, including RA, OA, AS and JIA. Conclusion: Curcumin and Curcuma longa Extract may improve symptoms and inflammation levels in people with arthritis. However, due to the low quality and small quantity of RCTs, the conclusions need to be interpreted carefully.